Cancers of the appendix: a case report and review of the literatures - Devi, Yumkhaibam Sobita; Daru, Himadri Kumar; Ponnas, Dulasiraman; Raj, Nithin; Goswami, Gaurav; Singh, Laishram Jaichand; Tamphasana, R. K. (International Journal of Research in Medical Sciences, 2016)
Cancers of the appendix are rare. Most of them are found accidentally on appendectomies performed for appendicitis. Majority of the tumors are carcinoid, adenoma, and lymphoma. Adenocarcinomas of appendix constitute about only 0.08% of all cancers and the treatment remains controversial. Here we are reporting a 57 year old man presented with symptoms of appendicitis, diagnosed with mucinious adenocarcinoma of the appendix. The patient was treated with appendectomy. We performed a review of literature on tumors of the appendix. Benign conditions are treated with surgery alone. For lymphomas chemotherapy are required and carcinoid syndrome can be treated with somatostatin analogues.